Limits to Tourism and Recreation in Water Catchments - Hughes, Michael; Carlsen, Jack (University of Tasmania, 2010)
Increase attention has been focussed on tourism and recreation access to public lands reserved for specific purposes, such as water catchments. Land based activities such as hiking, horse riding, motor and mountain biking, abseiling and off-road driving as well as water based activities (canoeing, fishing, swimming) have all been deemed by water managers as a risk to drinking water quality. Increasing demand has increased pressure for tourism and recreation access to these areas. The question then becomes, what level of risk to drinking water quality is posed by these activities? Also, what is the most appropriate management regime for tourism and recreation in water catchments?This paper is based on a review of the legislative, historical and current framework for managing public water catchment areas and drinking water sources in South Western Australia. The review includes an assessment of catchment management regimes in other states of Australia as well as in the United Kingdom and Canada. Management regimes range from total exclusion (as practiced in Western Australia) to managed tourism and recreation use of water catchments (as in Queensland and Victoria). Management of water catchments requires high levels of co-operation between government agencies responsible for land management, water quality and tourism and recreation and the adoption of integrated catchment management strategies is essential.